2019
DOI: 10.3168/jds.2019-16447
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative effect of Lactobacillus plantarum Y44 on 2,2′-azobis(2-methylpropionamidine) dihydrochloride (ABAP)-damaged Caco-2 cells

Abstract: Some Lactobacillus strains have been reported to have antioxidative activity. In our previous work, we screened Lactobacillus plantarum Y44 for its antioxidative activity. In this study, we further studied the antioxidative activities of L. plantarum Y44 using chemical antioxidant methods, including the 2,2-diphenyl-1-picrylhydrazyl and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) free radical scavenging assays, the ferric reducing antioxidant power test, and oxygen radical absorbance capacity test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
1
30
0
2
Order By: Relevance
“…69 The FRAP test has been used to evaluate the antioxidant capacity of L. plantarum Y44 in Caco-2 cells damaged with 2,2′-azobis (2-methylpropionamidine) dihydrochloride in vitro, which revealed that L. plantarum Y44 exerted antioxidative effects in a dose-dependent manner. 84 The total antioxidant capacity in the livers of hyperlipidemic rats significantly increased after L. casei supplementation as indicated by a FRAP assay. 87 FRAP assays have been also used to compare the antioxidant capacities of fresh skimmed, pasteurized, and UHT milks before and after fermentation with several lactobacilli combined or not with the yeast Saccharomyces boulardii.…”
Section: Assays Based On the Dynamics Or End Products Of Redox Processesmentioning
confidence: 98%
See 2 more Smart Citations
“…69 The FRAP test has been used to evaluate the antioxidant capacity of L. plantarum Y44 in Caco-2 cells damaged with 2,2′-azobis (2-methylpropionamidine) dihydrochloride in vitro, which revealed that L. plantarum Y44 exerted antioxidative effects in a dose-dependent manner. 84 The total antioxidant capacity in the livers of hyperlipidemic rats significantly increased after L. casei supplementation as indicated by a FRAP assay. 87 FRAP assays have been also used to compare the antioxidant capacities of fresh skimmed, pasteurized, and UHT milks before and after fermentation with several lactobacilli combined or not with the yeast Saccharomyces boulardii.…”
Section: Assays Based On the Dynamics Or End Products Of Redox Processesmentioning
confidence: 98%
“…In vitro experiments using human Caco-2 colorectal cells have shown that L. plantarum Y44 can elevate catalase expression in cells damaged by 2,2′-azobis (2-methylpropionamidine) dihydrochloride. 84 Another study using an in vitro model of enterocytes investigated the modulation of L. casei Shirota on the expression of gastro-intestinal GSH peroxidase in enterocytes. 85 Human patients with type 2 diabetes that consumed yogurt containing L. acidophilus LA5 and B. animalis subsp.…”
Section: Enzymatic Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the interesting probiotics aspects, some Lactobacillus strains have been reported to have antioxidant properties by decreasing the level of oxidants such as reactive oxygen species (ROS) [68]. The DPPH assay is generally used in vitro to determine the scavenging activity, and is one of the most sensitive, common and reliable methods [69].…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] In vitro studies have shown an effect of Lactobacillus on Nrf2. [53][54][55] A putative mechanism may be proposed (Figure 2). SARS-CoV-2 downregulates ACE2 inducing an increased insulin resistance associated with oxidative stress through the AT 1 R pathway.…”
Section: Proposed Mechanisms Of Action Of Kimchi and Fermented Vegetamentioning
confidence: 99%